The Greeks and their Eastern Neighbours. Studies in the Relations between Greece and the Countries of the Near East in the Eighth and Seventh Centuries B.C. - Dunbabin, Thomas James (1957)
With a foreword by Sir John Вeazleу. Edited by John Воardmаn. As Supplementary Paper No 8 published by the Society for the Promotion of Hellenic Studies.